Analysis of Income And Marketing Efficiency Of Gouramy In Yeh Embang Kangin Jembrana Village - I Wayan Sudana (Warmadewa University Press, 2020)
Gouramy is one of the freshwater fisheries commodities that has good prospects to be developed, the price never goes down and trends to increase because the market demand for this commodity is quite high. This study was conducted to determine the pattern of gouramy marketing channels, the amount of margins, farmer shares and marketing efficiency in farmer groups in Yeh Embang Kangin Village in 2019. The data used are qualitative and quantitative data, while based on their sources the primary and secondary data collected with interview and documentation methods for further analysis with descriptive analysis techniques with quantitative approaches. The results showed that the marketing of gouramy in Yeh Embang Kangin Village had the same marketing pattern, from farmers to collectors to retailers to consumers. Total margin of Rp. 12,000 / kg and 73.3% farmer share. And the value of farmer share is greater than the total margin. Based on the calculation of marketing efficiency, marketing efficiency is obtained at 12.4% so that it can be said that marketing gouramy with the marketing pattern used is classified as efficient.